The effect of environmental temperature on influence line of concrete beam type bridge. (February 2023) - He, Wen-Yu; Li, Zhidong; Zhou, Lei; Ren, Wei-Xin; Li, Yifan
Abstract: The influence line (IL) contains information induced by a unit force applied at any cross-section of the bridge, and its change can be used for damage identification. However, environmental temperature will also change the bridge IL, thus affect the damage identification effectiveness. In this paper, the main factors affecting the deflection and strain ILs of the concrete beam type bridges are systematically studied considering that temperature affects the structural static characteristics by changing the elastic modulus of concrete material, structural geometry, boundary condition and axial force. Then, based on the analytical formulas of the deflection and strain ILs of the concrete beam type bridge, the iterative calculation formulas describing the relationship between the ILs and the temperature are derived. Finally, the iterative calculation formulas are verified by numerical examples of beams with equal and variable cross-sections, and experiment in Environmental Coupling Test Chamber. The deflection and strain ILs are identified by parking a vehicle at different locations on the bridge progressively in the experiment. The results indicate that the maximum absolute values of the relative change rate (RCR) of the Ils are even up to 10%, and the effect of environmental temperature on the IL concrete beam type bridge cannot be ignored. The proposed iterative calculation formulas can effectively consider the effect of environmental temperature, and reduce the maximum absolute values of the RCR of the Ils to be less than 1%. Thus it can be used to calculate the IL of concrete beam type bridges under actual temperature.